Urachal adenocarcinoma with cervical invasion misdiagnosed as primary cervical adenocarcinoma: a case report and literature review - Wang, Yiran; Li, Maomao; Yang, Kaixuan (Frontiers in Oncology, 2024)
BackgroundUrachal carcinoma (UrC) is a rare malignancy with no known specific early symptoms. It is often diagnosed at advanced stages and is associated with poor prognosis.Case presentationThis study presents a rare case of urachal adenocarcinoma (UrAC) invading the bladder and vagina in a female patient. Initially, the patient was misdiagnosed as having a primary cervical adenocarcinoma 2.5 years prior. Subsequently, anterior pelvic exenteration and bilateral ureterocutaneostomies were performed. Twenty months after the first surgery, the patient was diagnosed with rectal metastasis and received gemcitabine chemotherapy. After achieving a stable disease state, the patient underwent laparoscopic ultralow rectal anterior resection, ultralow anastomosis of the sigmoid colon and rectum, prophylactic transverse colostomy, and right common iliac and external iliac lymph node dissection. The patient then received a cycle of postoperative chemotherapy with oxaliplatin and capecitabine; however, treatment was stopped due to adverse reactions. The patient continues to receive regular follow-ups, and her general condition is good.ConclusionsUrC is rare, and preoperative differential diagnosis is difficult. This is the first report of UrC being misdiagnosed as cervical cancer. The presented case highlights the importance of accurate histopathological examination and comprehensive analysis. Anterior pelvic exenteration was also identified as a potentially effective treatment strategy for patients with local pelvic recurrence of UrC, although further investigation is required.